Cognitive impairment in rapid‐onset dystonia‐parkinsonism. Issue 3 (16th January 2014) - Cook, Jared F.; Hill, Deborah F.; Snively, Beverly M.; Boggs, Niki; Suerken, Cynthia K.; Haq, Ihtsham; Stacy, Mark; McCall, W. Vaughn; Ozelius, Laurie J.; Sweadner, Kathleen J.; Brashear, Allison
ABSTRACT: Rapid‐onset dystonia‐parkinsonism (RDP) is caused by mutations in the ATP1A3 gene. This observational study sought to determine if cognitive performance is decreased in patients with RDP compared with mutation‐negative controls. We studied 22 familial RDP patients, 3 non‐motor‐manifesting mutation‐positive family members, 29 mutation‐negative family member controls in 9 families, and 4 unrelated RDP patients, totaling 58 individuals. We administered a movement disorder assessment, including the Burke‐Fahn‐Marsden Dystonia Rating Scale (BFMDRS) and the Unified Parkinson's Disease Rating Scale (UPDRS) and a cognitive battery of memory and learning, psychomotor speed, attention, and executive function. The cognitive battery was designed to evaluate a wide range of functions; recognition memory instruments were selected to be relatively pure measures of delayed memory, devoid of significant motor or vocal production limitations. Comparisons of standardized cognitive scores were assessed both with and without controlling for psychomotor speed and similarly for severity of depressive symptoms. A majority of RDP patients had onset of motor symptoms by age 25 and had initial symptom presentation in the upper body (face, mouth, or arm). Among patients, the BFMDRS (mean ± SD, 52.1 ± 29.5) and UPDRS motor subscore (29.8 ± 12.7) confirmed dystonia‐parkinsonism. The affected RDP patients performed more poorly, on average, than mutation‐negative controls for all memory and learning, psychomotor speed, attention, and executive function scores (all P  ≤ 0.01). These differences persisted after controlling for psychomotor speed and severity of depressive symptoms. Impaired cognitive function may be a manifestation of ATP1A3 mutation and RDP. © 2014 International Parkinson and Movement Disorder Society